Use of Viral Load as a Surrogate Marker in Clinical Studies of Cytomegalovirus in Solid Organ Transplantation: A Systematic Review and Meta-analysis. - Natori, Yoichiro; Alghamdi, Ali; Tazari, Mahmood; Miller, Veronica; Husain, Shahid; Komatsu, Takashi; Griffiths, Paul; Ljungman, Per; Orchanian-Cheff, Ani; Kumar, Deepali; Humar, Atul (Clinical Infectious Diseases, 2018)
Symptomatic cytomegalovirus (CMV) disease has been the standard endpoint for clinical trials in organ transplant recipients. Viral load may be a more relevant endpoint due to low frequency of disease. We performed a meta-analysis and systematic review of the literature. We found several lines of evidence to support the validity of viral load as an appropriate surrogate end-point, including the following: (1) viral loads in CMV disease are significantly greater than in asymptomatic viremia (odds ratio, 9.3 95% confidence interval, 4.6-19.3); (2) kinetics of viral replication are strongly associated with progression to disease; (3) pooled incidence of CMV viremia and disease is significantly lower during prophylaxis compared with the full patient follow-up period (viremia incidence: 3.2% vs 34.3%; P < .001) (disease incidence: 1.1% vs 13.0%; P < .001); (4) treatment of viremia prevented disease; and (5) viral load decline correlated with symptom resolution. Based on the analysis, we conclude that CMV load is an appropriate surrogate endpoint for CMV trials in organ transplant recipients.
EVALuna2:35295